Otimização do setor de prensagem por meio de planejamento de produção em uma industria de papel - Drummond, Daniela Medeiros Devienne, 1974- (2008)
Orientadores: Reginaldo Guirardello, Maria Teresa Moreira Rodrigues, Ignacio E. Grossmann